Contribuições da análise autorreflexiva dos relatórios de estágio na formação em Licenciatura em Língua Inglesa - Santos, Hosana Pereira de Sousa (Universidade Federal do Tocantins, 2020)
The present monograph deals with a research on self-reflection, from my internship reports, requested by the English Language Arts course, through an analysis of them. Based on these analyses, the objective is to answer how the reflexive reports can contribute to the English teachers’ formation. Throughout the research, we could observe an evolution on the theme and perceive how to face each obstacle. The difficulties encountered in relation to the prevailing educational system and the contact with teachers and students from the schools proved to be very enriching. As a research methodology, we carry out a bibliographical and documentary research. In the interpretation of the data, we used the qualitative approach, which allowed for a self-reflexive analysis of the internship reports, with a focus on contributing to my training. Given this, we find that the Supervised Internship is an important moment of the course, which allows us to have a more comprehensive vision regarding the future teaching profession.